Persepsi masyarakat tempatan mengenai pasca Rainforest World Music Festival - Joshua, Anak John Bujang. (Universiti Malaysia Sarawak (UNIMAS), 2019)
This research is related to the perception of the local community in Sarawak on the Rainforest World Music Festival (RWMF) held annually at Kampung Budaya Sarawak. This study has been using the full quantitative method to get the results of the study. The research instrument used in collecting data is a questionnaire questionnaire which likert scale. The importance of this research is to improve RWMF in collaboration with the organizers.